Efeito do revestimento organomineral em sementes de Urochloa brizantha cv. Marandu - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The study addressed the physical and physiological aspects of Urochloa brizantha cv. Marandu seeds, a variety widely used in tropical grazing systems due to its adaptability and benefits to soil and animal productivity. The objective was to evaluate the effect of the organomineral coating on the seeds of this variety, considering its influence on germination, viability, and vigor. The research will be conducted through laboratory and greenhouse experiments, analyzing variables such as temperature, humidity, and light, in addition to testing different storage conditions. It is expected that the organomineral coating will contribute to seed protection, promoting greater uniformity in germination and better initial seedling development. These results may support more efficient management practices, optimizing the use of forage seeds and ensuring sustainability in pasture establishment.
Effect of organomineral coating on seeds of Urochloa brizantha cv. Marandu
Keywords: Braquiaria; Germinação; Gramíneas; Forragicultura; Brachiaria; Germination; Grasses; Forage farming; CIENCIAS AGRARIAS